Effectiveness of Education Through TikTok Social Media in Increasing Anemia Understanding Among Adolescent Girls: A Literature Review - Salsabilla Cathabell Yudinda; Aristanto Prambudi; Ahmad Syarif (Journal of Diverse Medical Research : Medicosphere, 2026)
Anemia remains a common health issue among adolescent girls, affecting their quality of life and academic performance. Conventional educational methods are often ineffective for the digital generation, making TikTok a potential alternative platform for engaging health education. This systematic literature review, based on the PRISMA 2020 framework, evaluated the effectiveness of TikTok-based educational interventions in improving knowledge and attitudes regarding anemia prevention among adolescent girls. Article searches were conducted through PubMed, Google Scholar, ResearchGate, and Mendeley for publications from 2021 to 2025, yielding seven studies that met inclusion criteria. Most studies reported increased knowledge following intervention, with average improvements of 20–45%. Six of seven articles demonstrated statistically significant effects on knowledge and attitudes. Short video formats combining visual and audio elements facilitated comprehension and information retention. Integrating TikTok with supporting media such as infographics improved understanding by up to 30% compared to using a single medium. In conclusion, TikTok is an effective medium for delivering health education on anemia to adolescent girls.